PENGARUH BEBAN KERJA MENTAL TERHADAP KINERJA WAITERS DI KAFE MANDJA PROGO BANDUNG DENGAN METODE NASA-TLX - Fadly Rizky Dermawan; Dony Sastra Danuatmaja (Universitas Widyatama, 2024)
The aim of this study is to measure and analyze the mental workload experienced by waiters at Kafe Mandja Progo Bandung, using the NASA-TLX method. The café and restaurant industry in Bandung is experiencing rapid growth, and Kafe Mandja on Jalan Progo has become a favorite destination for locals and tourists alike. However, behind this popularity, waiters face significant challenges of high mental workload, which can affect their performance and productivity. The NASA-TLX method, which measures six main dimensions (Mental Demand, Physical Demand, Temporal Demand, Own Performance, Frustration Level, and Effort), is employed to evaluate the mental workload. The research findings indicate that the average Workload Level (WWL) of waiters at Kafe Mandja Progo exceeds the threshold of 80, indicating a high mental workload. Therefore, action is needed to reduce this workload through task redistribution, hiring new staff, and routine monitoring of mental and physical well-being. Implementation of these strategies is expected to enhance work efficiency, reduce fatigue, and improve service quality at Kafe Mandja. This study provides valuable insights for management to design policies that support employee well-being and performance, and contributes to a deeper understanding of workload management in the culinary industry. Keywords : Mental workload, NASA-TLX, Waiters, Waiters performance